2019
DOI: 10.2147/ndt.s198559
|View full text |Cite
|
Sign up to set email alerts
|

<p>2D-DIGE as a strategy to identify serum protein biomarkers to monitor pharmacological efficacy in dopamine-dictated states of Parkinson&rsquo;s disease and schizophrenia</p>

Abstract: Objectives Parkinson’s disease and schizophrenia are clinical scenarios that occur due to dopaminergic deficit and hyperactivity in the midbrain, respectively. Current pharmacological interventions for these two diseases therefore aim to restore normal dopamine levels in the midbrain. But during therapy, there is a overshooting of dopamine concentrations that result in hallucinations in Parkinson’s disease patients and extra-pyramidal symptoms in schizophrenic patients. This causes a lot of inconv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This turnover is a response mechanism to counter the damage at synaptic terminals because of inflammation or oxidative stress, both of which are elevated in Parkinson’s disease 77. In a previous study by our group, the level of alpha-2-macroglobulin was found to be elevated in Parkinson’s disease as compared to schizophrenia 22. Interestingly, LRP is a common receptor for apolipoprotein E, alpha-2-macroglobulin and amyloid precursor protein 78.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This turnover is a response mechanism to counter the damage at synaptic terminals because of inflammation or oxidative stress, both of which are elevated in Parkinson’s disease 77. In a previous study by our group, the level of alpha-2-macroglobulin was found to be elevated in Parkinson’s disease as compared to schizophrenia 22. Interestingly, LRP is a common receptor for apolipoprotein E, alpha-2-macroglobulin and amyloid precursor protein 78.…”
Section: Discussionmentioning
confidence: 82%
“…The unavailability of reliable biomarkers to monitor drug therapy in Parkinson’s disease and schizophrenia provides opportunities for clinical proteomic-based biomarker discovery in this field. In the recent past, our group has been dedicatedly involved in protein biomarker discovery to assess treatment in both Parkinson’s disease and schizophrenia 21,22…”
Section: Introductionmentioning
confidence: 99%